Efficient Management of Expenditure in Healthcare - Lazarov, Lachezar (Research Papers, 2018)
The article aims to highlight the importance of health care spending and to focus on their cost-effective spending as one of the main tools for achieving balance and justice in the healthcare system in Bulgaria. The tasks to achieve the goal are related to the presentation of health-demographic indicators of a number of European countries including Bulgaria and the expended funds for health. The research period is 20 years. from 1995 to 2014. The goal is achieved through comparative approach and analysis. The results obtained make it possible to make adequate and timely management decisions in the sphere of healthcare.
Keywords: Effective management; Health costs; Direct payments; Health systems; Control